NESC preprint - Preprint Proposals for the 2028 Edition of the National Electrical Safety Code (NESC) (IEEE, 2025)
This Preprint provides the full text of each change proposal (CP) to revise the 2023 Edition of the National Electrical Safety Code (NESC), together with the initial recommendation of the subcommittee that has jurisdiction over the rule addressed by the CP. The purpose of the NESC 2028 Preprint is to solicit public comment for each of the CPs and initial Subcommittee actions. The public comment period is 1 July 2025 to 24 March 2026. Subcommittees will consider the original change proposal, the initial recommendations, and public comment to develop final recommendations in the Fall of 2026, for final approval by the NESC Main Committee in 2027.
Keywords: High voltages.